Understanding decision making about balancing two stocks: the faculty gender balancing task. (30th June 2016) - Bleijenbergh, Inge; Vennix, Jac; Jacobs, Eric; van Engen, Marloes
Abstract: This paper contributes to the understanding of dynamic decision making by exploring how people understand the dynamic system underlying a task with modest dynamic complexity. Using the faculty gender balancing task, we experimentally test the extent to which participants correctly estimate the inflow needed to balance two unbalanced stocks and how they substantiate their decision. The results, based on performance data for 133 participants, show that people have difficulty determining the correct hiring percentage. Three‐quarters of the participants recommended a hiring percentage that was too low to balance the stocks in time or to balance them at all. Analysis of the substantiations showed that nearly half of the participants underpinned their decision with calculations, while 45 percent used intuitive estimations. The calculations seem to be based on three heuristics, reasoning patterns on which participants erroneously relied to assess dynamic behavior. Contrary to what has been found so far, the participants who used intuitive estimations to support their decisions performed relatively better on the task. © 2016 The Authors. System Dynamics Review published by John Wiley & Sons Ltd on behalf of System Dynamics Society